2021
DOI: 10.7717/peerj.10185
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparison of four MRSA clinical isolates from Germany and Hungary

Abstract: Staphylococcus aureus is a drug-resistant pathogen, capable of colonizing diverse ecological niches and causing a broad spectrum of infections related to a community and healthcare. In this study, we choose four methicillin-resistant S. aureus (MRSA) clinical isolates from Germany and Hungary based on our previous polyphasic characterization finding. We assumed that the selected strains have a different genetic background in terms of the presence of resistance and virulence genes, prophages, plasmids, and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 126 publications
2
12
0
Order By: Relevance
“…In addition, when investigating phage-antibiotic synergy, many studies rely on single or few reference strains or clinical isolates only as being representative for the whole species. However, given the genetic and phenotypic heterogeneity of opportunistic pathogens and even laboratory strains [16][17][18][19], it is important to test the suitability of potential phage-antibiotic pairs on a larger set of bacterial isolates. In this study, we tested the hypothesis that oxacillin, the antibiotic of choice against Methicillin-susceptible S. aureus (MSSA), and phage Sb-1, a member of the Twort-like viruses, exert stronger activity against MRSA in combination than either antimicrobial substance alone.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when investigating phage-antibiotic synergy, many studies rely on single or few reference strains or clinical isolates only as being representative for the whole species. However, given the genetic and phenotypic heterogeneity of opportunistic pathogens and even laboratory strains [16][17][18][19], it is important to test the suitability of potential phage-antibiotic pairs on a larger set of bacterial isolates. In this study, we tested the hypothesis that oxacillin, the antibiotic of choice against Methicillin-susceptible S. aureus (MSSA), and phage Sb-1, a member of the Twort-like viruses, exert stronger activity against MRSA in combination than either antimicrobial substance alone.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 65 analyzed prophages, 57 prophages were extracted from methicillin-resistance S. aureus (MRSA) strains, while the 8 analyzed prophages were extracted from methicillin-sensitive S. aureus (MSSA) strains in which 4 prophages were from 4 MSSA strains ( S. aureus HD1410, S. aureus I3, S. aureus SA13-192, and S. aureus SA14-639)-associated with human infections, and another 4 prophages were extracted from 4 MSSA strains ( S. aureus 483, S. aureus 909, S. aureus C3489, and S. aureus C5086)-associated with bovine and dog infections. Among the MRSA strains, SA G6, and S. SA G8 strains were reported earlier as hospital-associated MRSA (HA-MRSA) 25 , while the other MRSA strains carried Staphylococcal Cassette Chromosome mec ( SCCmec ) types IV, and V which are regarded as community-associated-MRSA (CA-MRSA) 26 . The MLST analysis result revealed that S. aureus strains associated with the animal infections have sequence types ST398 (clonal complex, CC398) and ST151 (CC151), while the S. aureus strains associated with human infections have ST398 (CC398), ST8 (CC8), ST5 (CC5), etc.…”
Section: Resultsmentioning
confidence: 99%
“…The clades were shaded with different colors and the prophage names labeled in black, red, and blue colors represent the prophages extracted from the S. aureus associated with Homo sapiens , Bos tourus , and Canis lupus familiaris , respectively. And the prophage names labeled in green color represent the prophages extracted from our previous study 25 , 27 . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations